Deriving Keratinocyte Progenitor Cells and Keratinocytes from Human‐Induced Pluripotent Stem Cells. (3rd August 2020) - Ibrahim, Michel R.; Medhat, Walid; El‐Fakahany, Hasan; Abdel‐Raouf, Hamza; Snyder, Evan Y.
Abstract: Skin or hair loss (alopecia) may occur due to a wide variety of causes ranging from trauma to pathological processes including acquired or congenital causes. It would be ideal to replace them with immunologically compatible cells to avoid potentially exacerbating the condition. Deriving the replacement cells from human‐induced pluripotent stem cells (hiPSCs) allows for sufficient scale up and using hiPSCs as the choice of human pluripotent stem cells (hPSC) will ensure immunocompatibility. Here we offer a protocol for differentiating hiPSCs into keratinocyte progenitor cells (KPC) and keratinocytes employing all‐trans retinoic acid (ATRA) and L ‐ascorbic acid, (L‐AA), bone morphogenic protein‐4 (BMP4), and epidermal growth factor (EGF). We observed that the hiPSC‐derived KPCs express the same panel of markers as primary hair follicle bulge stem cells (HFBSCs), including CD200, integrin α‐6 (ITGA6), integrin β‐1 (ITGB1), the transcription factor P63, keratin 15 (KRT15), and keratin 19 (KRT19). If permitted to differentiate further, the hiPSC‐derived KPC lose CD200 expression and rather come to express keratin 14 (KRT14) indicating emergence of more mature terminally‐differentiated keratinocytes. The HFBSCs are transplantable for hair follicle (HF) restoration, and the keratinocytes may be transplantable for therapy for large burns or ulcers. © 2020 Wiley Periodicals LLC. Basic Protocol 1 : Reprogramming of normal human skin fibroblasts into normal hiPSCs using episomal DNA cocktail Basic Protocol 2 : Differentiation of hiPSCs into KPCs and keratinocytes Alternate Protocol 2 : EBS formation protocol using AggreWell™ plates (Antonchuk, 2013) Support Protocol 1 : Passage hiPSC‐KPC Support Protocol 2 : Immunocytochemistry (ICC) Support Protocol 3 : Immunofluorescence staining of cells for flow cytometry (FC)